2015
DOI: 10.1038/ncb3266
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α is an endogenous substrate of endoplasmic-reticulum-associated degradation

Abstract: Endoplasmic reticulum (ER)-associated degradation (ERAD) represents a principle quality control mechanism to clear misfolded proteins in the ER; however its physiological significance and the nature of endogenous ERAD substrates remain largely unexplored. Here we discover that IRE1α, the sensor of unfolded protein response (UPR), is a bona fide substrate of the Sel1L-Hrd1 ERAD complex. ERAD-mediated IRE1α degradation occurs under basal conditions in a BiP-dependent manner, requires both intramembrane hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
222
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(251 citation statements)
references
References 54 publications
22
222
0
Order By: Relevance
“…We next explored how Sel1L deficiency in the ER of AVP neurons leads to systemic water imbalance. As in other cell types (20,21,27), Hrd1 protein levels were markedly reduced in Sel1L-deficient AVP neurons ( Figure 4A the axons toward synaptic terminals. We costained brain tissue sections with 2 different proAVP antibodies specifically recognizing AVP and NPII domains ( Figure 4E) (39,40) and found that at 1 week of age, there was already a notable reduction of AVP signal in the axons of Sel1L AVP neurons ( Figure 4F and Supplemental Figure 4).…”
Section: Sel1lmentioning
confidence: 83%
See 2 more Smart Citations
“…We next explored how Sel1L deficiency in the ER of AVP neurons leads to systemic water imbalance. As in other cell types (20,21,27), Hrd1 protein levels were markedly reduced in Sel1L-deficient AVP neurons ( Figure 4A the axons toward synaptic terminals. We costained brain tissue sections with 2 different proAVP antibodies specifically recognizing AVP and NPII domains ( Figure 4E) (39,40) and found that at 1 week of age, there was already a notable reduction of AVP signal in the axons of Sel1L AVP neurons ( Figure 4F and Supplemental Figure 4).…”
Section: Sel1lmentioning
confidence: 83%
“…Together, this complex is responsible for the degradation of a subset of misfolded proteins in the ER (11,12). Like its yeast counterpart Hrd3p (14), mammalian Sel1L is required for the stability of Hrd1 (20) and may both directly recruit substrates to Hrd1 (21) and regulate Hrd1 activity (22). Germline Sel1L or Hrd1 deficiency is embryonically lethal in mice (23,24), and acute global loss of Sel1L or Hrd1 in adult mice leads to premature death within 2 to 3 weeks (20,23), suggesting that Sel1L and Hrd1 are indispensable for both development and postnatal survival (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5 E and F), further confirming that Hrd1 protects B cells from AICD independent of UPR response. We have recently discovered that Hrd1 suppresses ER-stress-induced cell death through targeting the downstream ER-stress sensor IRE1α for ubiquitination and degradation (27,28). However, further deletion of IRE1α in Hrd1 KO mice could not rescue the reduction in the peripheral B cells in spleen (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to a previous study, this may be DDRGK1 independent in BL, as DDRGK1 expression was negatively correlated with IRE1α stability in P493 cells (Supplemental Figure 2I). In addition, Sun et al demonstrated that IRE1α is a substrate of the SEL1L-HRD1 ERAD complex and that ERAD-mediated IRE1α degradation is attenuated by ER stress (22). However, no significant changes in SEL1L1 or HRD1 protein levels were observed in P493 cells with variable c-Myc expression (Supplemental Figure 2, J and K), suggesting that the exact mechanism of how c-Myc regulates IRE1α protein stability needs to be further investigated.…”
Section: Introductionmentioning
confidence: 91%